Scourability of Undisturbed Soils of Different Land Use Types in Loess Hilly Region Under Natural Freezing and Thawing Conditions - Bo Lanfeng; Li Zhanbin; Ma Bo; Xiao Lie (Shuitu baochi tongbao)
[Objective] The effects of freezing and thawing on soil erosion resistance of three land use types (sloping farmland, grassland, and shrub land) were studied in order to provide a theoretical basis for vegetation restoration and construction in the seasonal freezing and thawing area of the Loess Plateau. [Methods] Based on a series of natural freezing and thawing cycles, field monitoring, and undisturbed soil scouring tests, the effects of freezing and thawing on soil erosion resistance of the three aforementioned land use types were determined. [Results] ① Compared with sloping farmland, the degree of freezing for grassland and shrub land was lower, and with shrub land having the lowest freezing degree and the best frost resistance. ② Freezing and thawing aggravates soil loss in varying degrees and reduces soil erosion resistance. The anti-scourability coefficient of grassland and shrub land was significantly higher than that of sloping farmland, indicating that vegetation coverage can effectively improve frost resistance and anti-scourability of soil under freeze-thaw conditions. ③ The total sediment loss before and after freezing and thawing for grassland and shrub land increased by 31% and 16.5%, respectively, and the anti-scourability coefficient decreased by 23% and 14%. The increase of sediment loss in grassland during freezing and thawing was higher, and the anti-scourability coefficient decreased the most. [Conclusion] Due to seasonal freezing and thawing of grassland and shrub land, the degree of grassland freezing is more severe, and the erosion resistance of grassland soil is worse than that of shrub land soil. Grassland may have a higher risk of soil erosion due to the seasonal freezing and thawing process.